Gambaran pemahaman kesehatan lingkungan sekolah dan perilaku hidup bersih dan sehat di SDN Tombolok kecamatan Pallangga kabupaten Gowa - Ridjal, Andi Tilka Muftiah; Zamaa, Muhammd Sahlan; Akbar, Reynaldi; Renaldi M (Institute for Advanced Science, Social, and Sustainable Future, 2024)
School environmental health is a condition of the school environment that can support the optimal growth and development of students in healthy living behavior and avoid negative influences. Clean and healthy living behavior at school is a set of behaviors practiced by students, teachers, and the school community based on awareness as a result of learning so that they can independently prevent disease, improve their health, and play an active role in creating a healthy environment. Objective to describe an understanding of the health of the school environment and clean and healthy living behavior. This research is a descriptive survey with a population of 104 students from grades 4, 5, and 6 of SDN Kunciok. The sampling technique used the total sampling method, and the research instrument used a questionnaire distributed to each respondent. The characteristics of student respondents based on the variable understanding of environmental health were in the poor category as many as 56 people (53.8%). In comparison, in the good category, there were 48 people (46.2%). Based on the PHBS variable, there were 53 people in the poor category (51.0%), while in the good category there were 51 people (49.0%). The majority of students have a poor understanding of the health of the school environment and clean and healthy living behavior. It is recommended that students who behave well must be able to maintain it, by not throwing rubbish carelessly, eradicating mosquitoes, using healthy latrines, and exercising regularly and in a measured manner, and for students who behave badly, they must be able to improve further to prevent environmental pollution that potentially cause disease.